FAKTOR-FAKTOR YANG MEMPENGARUHI SUKU BUNGA DEPOSITOBERJANGKA DUABELAS BULAN PADA BANK PEMERINTAH INDONESIA PERIODE 2005-2015FAKTOR-FAKTOR YANG MEMPENGARUHI SUKU BUNGA DEPOSITOBERJANGKA DUABELAS BULAN PADA BANK PEMERINTAH INDONESIA PERIODE 2005-2015 - Siti Nurjanah; Tri Sukirno Putro; Anthony Mayes (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
This research aims to find out how to the influence of interst rates of BI Rate, inflation and loan to deposit ratio (LDR) towards twelve month term deposit interest rates at Indonesia’s goverment bank. This research uses secondary data obtained from the data Banking Statistics Indonesia and the Indonesian Financial Statistics published in the statistical data of Bank Indonesia from 2005 to 2015 time span. The analytical method used is multiple regression analysis. Testsconducted on the hypothesis and the reliability of the data (assuming classical) using significance level of 5%. These results indicate the BI Rate positive and significant impact on interest rates of time deposits as evidenced by the positive tvalue of 4.364 and a significant value 0.003 <0.05. Inflation is negative and significant effect on the interest rates on time deposits as evidenced by the negative t value of -2.486 and significant value of 0.042 <0.05. LDR and no significant negative effect on interest rates on time deposits as evidenced by the negative t value at -0945 and significant value of 0.376> 0.05.Keywords: Interest BI Rate, Inflation, LDR (Loan to Deposit Ratio) and Deposit Interest Rates